Perancangan Sistem Informasi Pembuatan Surat Pengantar Di Desa Waleng (Studi Kasus: Kelurahan Waleng) - Galuh Aji Gautama; M. Setiawan; Febrianta Surya (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The design of a cover letter creation system is very important for the transition to technology-based village governance, increasing efficiency, accuracy and accessibility in administrative data management. In Waleng Village, making cover letters is still using the manual method, prone to human error. To optimize web-based public services in the digitalization era, a system was developed using the Rapid Application Development (RAD) method. This information system research uses qualitative research and testing it with blackbox testing and reveals that this information system can optimize submission of cover letters online and functions as a database for cover letter applications. Regular maintenance of software and hardware is necessary to ensure optimal consistency in the use of information.